Image-guided confirmation of a precision pull-through procedure during laparoscopically assisted anorectoplasty in an open MRI operating theater: first application in an infantile case with anorectal malformation - Shun Onishi; Chihiro Kedoin; Masakazu Murakami; Nayuta Higa; Akihiro Yoshida; Kazutoshi Onitsuka; Takahiro Moriyama; Koji Yoshimoto; Satoshi Ieiri (Surgical Case Reports)
Abstract Background Image-guided surgery with an open magnetic resonance imaging (MRI) system is applied for brain tumors in the neurosurgery field, but has rarely been reported in pediatric surgery. We report our initial experience of intraoperative confirmation of precision rectal pull-through during laparoscopically assisted anorectoplasty (LAARP) in an open MRI operating theater for pediatric patients with anorectal malformation (ARM). Case presentation A 3.0 kg term male neonate was delivered with anorectal malformation. An invertogram revealed the intermediate type. Transverse colostomy was made on the left upper abdomen. The recto-bulbar urethral fistula (RBUF) was diagnosed by a distal colostogram and voiding cystourethrogram. LAARP was planned at 6 months of age. Because this was the first procedure in which the pediatric abdomen had been scanned in an open MRI operating theater in our institution, we scanned his pelvic floor under sedation 3 weeks before the operation using the open MRI system in our operation room. We performed the operation with 4 trocars. The peritoneal reflection was carefully incised and the rectum was dissected. The RBUF was resected. The center of the muscle complex was detected at the perineal skin with an electrical nerve stimulator, and a 7-mm longitudinal skin incision was made on the perineal lesion for anoplasty. The muscle complex and the pubo-rectal sling were confirmed laparoscopically using a 3.5-mm bipolar forceps connected to the electrical nerve stimulator. Anoplasty was performed between the rectal stump and perineal skin. After anoplasty, the patient was scanned with open MRI under general anesthesia. We attached the quadrature-detection (QD) head coil around the patient’s pelvis and inserted him in the gantry. A 0.45-T open MRI clearly revealed that the pulled through rectum was located in the center of the muscle complex on T2-weighted images. The postoperative course was uneventful. Oral intake was started on post-operative day 1. Postoperative dynamic urography showed no complication (e.g., leakage or residual fistula). Conclusions We successfully performed LAARP for ARM, with intraoperative confirmation of precision rectal pull-through in an open MRI operating theater. Further cases are required to evaluate the application of open MRI systems in pediatric surgery.